Development of LVEP-Based IPAS Monopoly Media to Improve Nationalist Character on Grade IV Elementary School Students - Vita, Rima Widya Nugraha; Apriani, An-Nisa; Sari, Indah Perdana; Aryani, Yusinta Dwi (Universitas Muhammadiyah Yogyakarta, 2024)
The problem studied in this research is the lack of use of learning media that incorporates the Living Values Education Program (LVEP) and nationalist character by teachers, and there are still moral deviations from students, which illustrates the lack of strengthening of nationalist character. The aims of this research are 1) to produce LVEP-based IPAS monopoly media on the material